Promote identification or prevent expansion? The effect of uploader-viewer similarity on viewer inspiration in the context of short video community - Fu, Senhui; Dai, Haiwen (Frontiers in Psychology, 2023)
Introduction Short video communities have proliferated recently, opening up a new channel for the promotion of online businesses. The main challenge in marketing with short videos is how to inspire consumers. Methods This study employs viewer social identification and self-expansion as its entrance point to to explain how uploader-viewer similarity affects viewers’ short video inspiration. We use empirical investigation method based on the data of 310 short video viewers to test our conceptual model. Results We found that there is a double-edged relationship between uploader-viewer similarity and short video inspiration. Particularly, uploader-viewer similarity enhances perceived social identification while reducing perceived self-expansion. The association between Uploader-viewer similarity and short video inspiration is moderated by viewers’ cognitive demands. Discussion These results provide a new perspective for enterprises to manage the relationship between viewers and media.